Criterias of Cultural Policy-Making in Imam Khomeini’s Thought - Mojtaba Babakhani; Asghar Eftekhari (Taḥqīqāt-i Farhangī-i Īrān, 2016)
Culture is proposed as an important criterion in politics management which has been considered in various systems. althoughlots of cultural elements are forming gradually during the time and by the effect of different causes, one cannot ignore the role of government policies in organizing them. Therefore one of the important duties of government in Islamic society is to determine the principles and general policies in the scope of managing the culture of society. The cultural principles and policies of Islamic Republic of Iran, that are formed based on Islamic thoughts, of course should be designed and drawn upon these thoughts. Accordingly, the main question of the current research is that: what are the ruling principles in the cultural policy-making of Iran’s society? According to the operational approach of the researchers, Imam Khomeini’s theory has been chosen as the base of the research. For this purpose, the content analysis method is used to study his most important speeches in this realm and we have tried to represent a model in which explains the most important cultural policy-making principles in the view of Imam Khomeini.